Pariwisata Berkelanjutan: Menjaga Warisan Budaya dan Lingkungan untuk Masa Depan yang Harmonis - lasaiba, Mohammad Amin (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2020)
Sustainable tourism focuses on preserving cultural heritage and protecting the environment while supporting local economic growth. This study analyzes how sustainably managed tourism can contribute to preserving cultural heritage and reducing adverse environmental impacts through a comprehensive literature review. The findings indicate that tourism designed with sustainability in mind can provide economic benefits while preserving local cultural values and fragile natural ecosystems. However, significant challenges remain, including the environmental impacts of poorly managed tourism activities and the need for local community involvement in decision-making processes. The literature also highlights the need for more effective and integrated policies to ensure that tourism retains the cultural and environmental resources that are its main attractions. By adopting a holistic approach that integrates economic, social, and ecological interests, sustainable tourism can be a powerful tool for promoting cultural and environmental preservation while ensuring long-term benefits for local communities and the ecosystems in which they live